Effectiveness of video-based modelling to facilitate conversational turn taking of adolescents with autism spectrum disorder who use AAC. (2nd October 2018) - Thirumanickam, Abirami; Raghavendra, Parimala; McMillan, Julie M.; van Steenbrugge, Willem
Abstract: This study evaluated and compared the effectiveness of packaged video modelling (VM) and video self-modelling (VSM) interventions to develop conversational behaviors with four adolescents with autism spectrum disorder (ASD) who used augmentative and alternative communication (AAC). The study was conducted using an alternating treatments design nested within a multiple baseline design. The intervention effect was measured using Robust-Improvement Rate Difference (R-IRD). The results demonstrated that, overall, video-based modelling used in conjunction with a system of least prompts was effective in promoting conversation skills in adolescents with ASD who used AAC. Without the systematic instruction, R-IRD indicated that these techniques yielded only small to moderate intervention effects. The findings demonstrated the necessity of systematic instruction for this group of participants. This investigation provides preliminary evidence to support the use of packaged video-based modelling interventions to develop conversation skills in adolescents with ASD who use AAC systems.